Analisis Implementasi Bauran Pemasaran 7P Pada Bank Muamalat Kantor Cabang Batu - Erna Resmiatini; Insiati Aisyah Hapsari Imanika (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
In the midst of Indonesia's population, which is predominantly Muslim, Sharia Banks have begun to show significant developments. Seeing this, conventional banks have also begun adding sharia services in each of their products, in order to maintain the number of existing customers and expand market share. As the first sharia bank in Indonesia, Bank Muamalat Indonesia (BMI) continues its efforts to harmonize various strategies to win competition in the sharia banking industry, one of them is through the 7P’s Marketing Mix. Through this research, the application of the 7P’s marketing mix strategy at the Bank Muamalat Batu-Malang will be analyzed. This research is to add scientific studies in the field of marketing, especially related to the 7P’s Marketing Mix. This research was conducted using a qualitative approach. The results show that the Bank Muamalat Batu - Malang has implemented the 7P’s Marketing Mix well. Even so, it would be better if Bank Muamalat Batu - Malang synergized the 7P’s Marketing Mix that had been implemented, with developing a Customer Relationship Management (CRM) strategy.